Sustainability and public health nutrition at school: assessing the integration of healthy and environmentally sustainable food initiatives in Vancouver schools. Issue 13 (16th March 2015) - Black, Jennifer L; Velazquez, Cayley E; Ahmadi, Naseam; Chapman, Gwen E; Carten, Sarah; Edward, Joshua; Shulhan, Stephanie; Stephens, Teya; Rojas, Alejandro
Abstract: Objective: To describe the development and application of the School Food Environment Assessment Tools and a novel scoring system to assess the integration of healthy and environmentally sustainable food initiatives in elementary and secondary schools. Design: The cross-sectional study included direct observations of physical food environments and interviews with key school personnel regarding food-related programmes and policies. A five-point scoring system was then developed to assess actions across six domains: (i) food gardens; (ii) composting systems; (iii) food preparation activities; (iv) food-related teaching and learning activities; and availability of (v) healthy food; and (vi) environmentally sustainable food. Setting: Vancouver, Canada. Subjects: A purposive sample of public schools ( n 33) from all six sectors of the Vancouver Board of Education. Results: Schools scored highest in the areas of food garden and compost system development and use. Regular integration of food-related teaching and learning activities and hands-on food preparation experiences were also commonly reported. Most schools demonstrated rudimentary efforts to make healthy and environmentally sustainable food choices available, but in general scored lowest on these two domains. Moreover, no schools reported widespread initiatives fully supporting availability or integration of healthy or environmentally sustainable foods across campus. Conclusions: More work is needed in all areas to fully integrate programmes and policies that support healthy, environmentally sustainable food systems in Vancouver schools. The assessment tools and proposed indicators offer a practical approach for researchers, policy makers and school stakeholders to assess school food system environments, identify priority areas for intervention and track relevant changes over time.